2022
DOI: 10.55563/clinexprheumatol/ryp027
|View full text |Cite
|
Sign up to set email alerts
|

Onset and temporal sequencing patterns of comorbidity between lifetime major depression, panic disorder and fibromyalgia

Abstract: Objective Fibromyalgia (FM) is a syndrome of unknown aetiology characterised by chronic widespread musculoskeletal painand associated with high rates of psychiatric comorbidities, mainly mood and anxiety disorders. This study aims to determine the age at onset (AAO) and temporal sequencing patterns of FM and its frequent and distinguishable psychiatric comorbidities, the major depressive episode(s) (MDE), and panic disorder (PD). Methods Diagnosis of MDE and PD were assigned using the Structured Clinical Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The comorbidity between panic and depression was found to be the most significant in a population study [ 18 ]. Using data from the Initial Study of National Comorbidity, Roy-Byrne et al (2000) found a strong lifetime and current comorbidity between panic and depression [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The comorbidity between panic and depression was found to be the most significant in a population study [ 18 ]. Using data from the Initial Study of National Comorbidity, Roy-Byrne et al (2000) found a strong lifetime and current comorbidity between panic and depression [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, poor psychological outcomes include an increased risk of self-harm and/or suicidality, instability in mental health and the transfer of addictions to other substances. 9,10 Poor physical outcomes include weight regain or failure to lose weight; chronic nausea and/or vomiting; and acid reflux. [11][12][13] 1.1 | Common considerations for people living with obesity A significant number of bariatric surgery-seeking patients present with complex psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently demonstrated that poor mental health and unresolved psychological difficulties are significant predictors of a less successful physical and psychological outcome from surgery. For example, poor psychological outcomes include an increased risk of self‐harm and/or suicidality, instability in mental health and the transfer of addictions to other substances 9,10 . Poor physical outcomes include weight regain or failure to lose weight; chronic nausea and/or vomiting; and acid reflux 11–13 …”
Section: Introductionmentioning
confidence: 99%